(untitled) (Archive of Conferences, 2020)
After gaining independence, Uzbekistan has paid great attention to the education of young people, opening the door to great opportunities for them to become mature and well-rounded individuals. The harmony and commonality of national and universal values ??play a special role in the education of young people. At a time when the flow of information of pedagogical psychologists is constantly transmitted through communication networks, it is our responsibility to ensure security, to prevent risks and negative consequences. Our young people are free-thinking, free from any negative influences, consciousness, thinking, honestly assess the events in the family and the environment, and can express their free attitude to them, with their advanced ideas, examples family members, classmates, friends who can influence, have intellectual power, be diligent, knowledgeable, courageous and polite.